Implikatur Percakapan pada Novel KKN di Desa Penari Karya Simpleman - Mirnawati, Mirnawati; Salam, Salam; Sakinah, Sakinah (TITIK DUA: Jurnal Pembelajaran Bahasa dan Sastra Indonesia, 2024)
This study aims to describe the form of conversational implicature contained in the novel KKN in Desa Penari by Simpleman. This type of research is descriptive qualitative research. The data in this study are texts (sentences containing special, general, and scaled conversational implicatures). The data collection technique was obtained using the method of reading and note-taking technique. The data analysis technique is by identifying, classifying, describing and analysing. The results showed that there are special, general, and scaled conversational implicatures in the novel KKN in Desa Penari by Simpleman. The conversational implicature includes (1) special conversational implicature means agreeing, asking, asserting, complaining, refusing, reporting, and ordering, (2) general conversational implicature means agreeing, asking, asserting, complaining, refusing, and reporting, (3) scaled conversational implicature uses the words all, many, some, always, often, and sometimes.